2022
DOI: 10.1088/1361-6560/ac934c
|View full text |Cite
|
Sign up to set email alerts
|

DH-Mammo PET: a dual-head positron emission mammography system for breast imaging

Abstract: Objective: To develop a simultaneous PET-Optical (OPET) breast imaging dual-head PET subsystem, called DH-Mammo PET, for accurate, early diagnosis and efficacy assessment of breast cancer with high resolution and sensitivity. Approach: We developed a breast-dedicated PET based on LYSO crystal, silicon photomultiplier array and multi-voltage threshold sampling technique. It consists of two detector heads, each with a detection area of 216 mm × 145.5 mm. The distance between the detector heads is fixed at 120 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It employs roughly the same mammography apparatus as traditional mammography, but instead of a film cassette, the apparatus is outfitted with a digital receptor and a computer. Digital mammography is at least as accurate as traditional mammography, according to a number of studies (Shi et al, 2023).…”
Section: Significantmentioning
confidence: 99%
See 1 more Smart Citation
“…It employs roughly the same mammography apparatus as traditional mammography, but instead of a film cassette, the apparatus is outfitted with a digital receptor and a computer. Digital mammography is at least as accurate as traditional mammography, according to a number of studies (Shi et al, 2023).…”
Section: Significantmentioning
confidence: 99%
“…This is done in order to minimize the number of tissue layers that the Xray beam must pass through. In the process, radiation absorption is reduced and the highestquality image is generated (Shi et al, 2023). However, the examinee typically experiences pain during breast compression and immobility during mammography.…”
Section: Significantmentioning
confidence: 99%
“…By using geometrical considerations, the system matrix weights are much smaller for oblique LORs compared to less oblique LORs, and c) other research groups developing dual panel systems which do not incorporate DOI information report image resolutions on the order of (or even under) the crystal size [5]. Shi et al [6] have found that not including DOI information in the reconstruction for a dual-head system like ours does not change the in-plane resolution (parallel to the detector), but it only affects the axial resolution (perpendicular to the detector). Our results agree with those publications.…”
Section: Plos Onementioning
confidence: 99%
“…Consequently, early detection of the disease is recognized worldwide as a priority in health care for reducing breast cancer mortality. Positron Emission Mammography (PEM) is a valuable medical imaging technique to diagnose breast cancer, monitor patients in follow-up studies, image therapeutic response and discover recurrence [4][5][6]. It is based on the determination of the 3D distribution of a radiopharmaceutical in target organs or tissues, in the same manner as Positron Emission Tomography (PET) [2,3].…”
Section: Introductionmentioning
confidence: 99%